Effect of Graphene and Graphene Oxide on Airway Barrier and Differential Phosphorylation of Proteins in Tight and Adherens Junction Pathways - Sofie Van Den Broucke (Nanomaterials, 2021)
Via inhalation we are continuously exposed to environmental and occupational irritants which can induce adverse health effects, such as irritant-induced asthma (IIA). The airway epithelium forms the first barrier encountered by these agents. We investigated the effect of environmental and occupational irritants on the airway epithelial barrier in vitro. The airway epithelial barrier was mimicked using a coculture model, consisting of bronchial epithelial cells (16HBE) and monocytes (THP-1) seeded on the apical side of a permeable support, and human lung microvascular endothelial cells (HLMVEC) grown on the basal side. Upon exposure to graphene (G) and graphene oxide (GO) in a suspension with fetal calf serum (FCS), ammonium persulfate (AP), sodium persulfate (SP) and hypochlorite (ClO−), the transepithelial electrical resistance (TEER) and flux of fluorescent labelled dextran (FD4-flux), was determined. Exposure to graphene nanoparticles (GNPs) induced an immediate negative effect on the epithelial barrier, whereas ClO− only had a negative impact after 24 h of exposure. AP and SP did not affect the barrier properties. The tight junctions (TJ) network showed less connected zonula occludens 1 (ZO-1) and occludin staining in GNP-exposed cocultures. Functional analysis of the phosphoproteomic data indicated that proteins in the adherens junction (AJ) and TJ pathways showed an altered phosphorylation due to GNP exposure. To conclude, the negative effect of GNPs on the epithelial barrier can be explained by the slightly altered the TJ organization which could be caused by alterations in the phosphorylation level of proteins in the AJ and TJ pathway.